The Effect of Laser Soldering onto Intermetallic Compound Formation, Growth - Siti Rabiatull Aisha, Idris; Nabila, Tamar Jaya; Muhammad Asyraf, Abdullah (Springer, 2022)
Recently, the laser soldering method has been introduced among electronic manufacturers because of its superior properties such as non-contact and localised heating, quick rise and drop in temperature, and ease of automation compared to reflow soldering. This paper discusses the effect of laser soldering parameters on intermetallic compound formation and growth between lead-free solder alloy and copper substrate. The analysis was conducted for the type of laser used for heat-sensitive components and characteristics of the laser soldering process, which could promote or inhibit excessive growth of intermetallic compound formation.